Konceptualne dileme implementacije načel bolonjskega procesa - Kotnik, Rudi (Sodobna pedagogika, 2006)
The implementation of the principles of the Bologna process involves at least two aspects. One, on the state level, refers to the codification of the principles in legislation; the other refers to the way in which these principles are understood by universities. The state has a controversial role; it is the promoter of the quality of education and at the same time the representative of corporate interests in the global world. Consequently, it is changing the fundamental role of education in global society. The role of the autonomy of universities, as well, is controversial: it can protect academic standards against business and politics, and at the same time it maintains rigidity in relation to any creative changes. The paper is therefore an attempt at analysis to simultaneously show the creative potential of the Bologna process and the traps. A historical background is provided for this purpose, as well as a conceptual analysis of the key concepts. The conclusion drawn from this analysis is that higher education needs creative adjustments which demand a reflective approach to the assumptions and implications of the Bologna process. It seems that the mere adoption of prescribed packages of 'competencies' is counterproductive in our context as a transition country.
Keywords: bolonjski proces; izobraževalna politika; šolske reforme; visoko šolstvo; kompetentnost; kurikulum; curriculum